Prenatal thermal stress affects acute-phase proteins, heat shock protein 70, and circulating corticosterone in developing broiler embryos and neonates - Hanafi, S.a.; Zulkifli, I.; Ramiah, S.k.; Chung, E.l.t.; Awad, E.a.; Sazili, A.q. (Elsevier, 2022)
Higher or lower incubation temperature may impose some degree of stress on developing poultry embryos. This study was designed to delineate the effects of prenatal thermal stress on serum levels of acute-phase proteins (APPs), namely ceruloplasmin (CPN) and alpha-1-acid glycoprotein (AGP), the regulation of brain mRNA levels of heat shock protein (Hsp) 70, and serum levels of corticosterone (CORT) in embryos and neonatal chicks. Hatching eggs were subjected to three thermal treatments; (i) standard optimum temperature throughout (SS: 37.8 °C and 56 % RH), (ii) heat stress for 12 h daily (HS: 40.0 °C and 56 % RH), and (iii) cold stress for 12 h daily 18 (CS: 30.2 °C and 56 % RH). The heat and cold stress treatments were imposed from the 10th to the 18th day of incubation (ED). Results showed that thermal stress had a negligible effect on hatchability rate and body temperatures of neonatal chicks. The CS treatment was detrimental to embryonic growth. The HS treatment elevated AGP (ED 16, ED 18, and post-hatch day 1), CPN (on post-hatch day 1), and CORT (ED 14). On the contrary, the CS embryos had reduced AGP (ED14, ED16, ED18, and post-hatch day 1), CPN (ED 16), and CORT (ED 14, ED 16, ED 18). The brain mRNA levels of Hsp70 were upregulated throughout the experimental period in both the HS and CS embryos and chicks. Based on these modifications, AGP, together with Hsp70 mRNA expression, could be considered effective biomarkers useful to evaluate the magnitude and the time response of embryos and neonatal chicks to prenatal thermal stress. It is concluded that developing chicken embryos have the ability to evoke APPs, Hsp70 and CORT reactions which are important to cope with thermal stress.